Teriparatide (rhPTH1-34) Anabolic Therapy for Treatment of Type II Dens Fracture Non-union in Elderly Patients: Report of 5 Cases. Issue 1 (April 2016) - Nasto, Luigi Aurelio; Tamburrelli, Francesco Ciro; Pambianco, Virginia; Autore, Giovanni; Formica, Virginia Maria; Colangelo, Debora; Pola, Enrico
Introduction: Type II dens fracture is the most common cervical spine fracture type in elderly patients. Treatment options for this common injury include conservative management (i.e., hard collar or Halo Vest immobilization) or surgery. Delayed union or non-union is a frequent complication in elderly patients and is associated with an increased morbidity and mortality due to prolonged immobilization and hospitalization. The rhPTH1–34 (Teriparatide) is the recombinant form of the biologically active component of the human parathyroid hormone, currently approved for treatment of severe post-menopausal osteoporosis. However many in vitro studies have also demonstrated the efficacy of rhPTH1–34 in stimulating osteogenesis and bone healing and a few case reports have been published on its use in humans for treatment of fracture non-unions. The aim of this study is to report our successful experience with the use of rhPTH1–34 in the treatment of 5 cases of dens fracture non-union in elderly patients. Material and Methods: Five patients (age > 70, all females) diagnosed with type II C2 dens fracture non-union (no neurological compromise) were enrolled in this study. Fracture non-union was defined as non- healing at 9 months after injury and radiographic evidence of failed healing progression over the last 3 months. All patients had been treated conservatively with a hard collar. Patients were started on anabolic drug therapy with daily subcutaneous injection of rhPTH1–34 (Teriparatide, 20 ng/die) for 3 months. Regular clinical assessments and monitoring of serum levels of calcium, phosphorus, vitamin D, and alkaline phosphatase were undertaken throughout the treatment period. We describe the evolution of our cases over time with serial CT scan imaging as well as HRQoL questionnaires (VAS, SF-12, and Eq. 5D). Results: Successful complete fracture healing was achieved in all patients at 74.5 ± 4.4 weeks after the injury and at 10.2 ± 3.8 weeks after the start of the anabolic therapy. Mean VAS score at the end of the treatment was 2.4 ± 1.3 (from a baseline value of 6.8 ± 2, p < 0.02) in all patients, while the average SF-12 score was 42 ± 3.7 (PCS) and 61.5 ± 2.11 (MCS) (from a baseline value of 25.1 ± 2.12 and 43.2 ± 1.49, p < 0.04) and Eq. 5D was 0.798 ± 0.044 (from a baseline value of 0.396 ± 0.198, p < 0.03). Patients had normal serum calcium level (9.1 ± 0.9 mg/dl). No side effects related to the use of the anabolic therapy were noted in our patients. Conclusion: Our case series shows that rhPTH1–34 has induced successful bone healing in all our cases of type II dens fracture non-union. Bone healing has been demonstrated through CT imaging and also confirmed by clinical improvement of HRQoL measures. This is a potentially groundbreaking finding in management of elderly patients with upper cervical injuries and will deserve further study in future.